Propyl gallate and butylated hydroxytoluene influence the accumulation of saturated fatty acids, omega-3 fatty acid and carotenoids in thraustochytrids. (May 2015) - Singh, Dilip; Mathur, Anshu S.; Tuli, Deepak K.; Puri, Munish; Barrow, Colin J.
Highlights: Propyl gallate added to media decreased the ratio of DHA to saturated fat in a thraustochytrid species. Propyl gallate also increased the production of astaxanthin in the thraustochytrid strain studied. The strain studied, schizochytrium sp. S31, grew well on the low cost carbon source glycerol. Propyl gallate and butylated hydroxytoluence can increase carotenoid levels and decrease DHA in thraustochytrids. Abstract: Schizochytrium sp. S31 was shown to have potential for production of the functional food ingredients docosahexaenoic acid (DHA) and astaxanthin, with coproduction of biodiesel. Biomass and lipid levels were greater with glycerol than with glucose as carbon source. Addition of propyl gallate or butylated hydroxytoluene to the media resulted in increased biomass and lipid levels, with propyl gallate being the more effective of the two antioxidants. Medium supplementation with propyl gallate at 0.03% and glycerol as the carbon source resulted in enhanced biomass productivity (28.50 g L −1 ), lipid accumulation (24.87 g L −1 ) and astaxanthin levels (452.26 µg L −1 ).